Diversification des moyens de production des agriculteurs dans AICCRA-Sénégal - Thiaw, Moussa; Worou, Nadine; Wane, Abdrahmane (International Livestock Research Institute, 2025)
This study evaluates the strategies for diversifying the means of production among farmers in Senegal through AICCRA's radio programs. By disseminating relevant agro-climatic information, farmers have been able to diversify not only their crops but also their sources of income, thereby enhancing their resilience to climatic hazards. The key diversification strategies observed among the beneficiaries of the AICCRA project include: 1. Crop diversification enables farmers to spread the risks associated with climatic uncertainties, enhance the utilization of natural resources, and stabilize their incomes. A total of 69.12% of agro-advisory beneficiaries have adopted crop diversification. 2. Income diversification: Livestock has become a significant source of diversification, accounting for 37.76% of the income of treated producers. This sector was particularly strengthened through better livestock management, including pasture management and animal health improvements. Additionally, producers diversified their income by engaging more in trade (26.56%) and crafts (24.07%), generating alternative income streams that reduce their dependence on agriculture. 3. Adoption of Climate-Smart agro-ecological practices: Exposed producers adopted more sustainable agro-ecological practices such as sprinkler irrigation, residue management, and rainwater harvesting. These practices not only improved land productivity but also diversified natural resource management methods, reducing vulnerability to climate change. 4. Utilization of new agricultural techniques: The program led to an increased adoption of new agro-ecological practices, such as the use of improved seeds, appropriate fertilization, and modified technical itineraries. These innovations contributed to diversifying agro-ecological practices and optimizing crop yields while reducing excessive use of chemical inputs. 5. Improved Climate Risk Management: With access to relevant and tailored information, 94% of beneficiaries understand the importance of rainfall for agricultural planning. This knowledge directly influenced crop diversification, allowing farmers to select varieties resistant to climate variations and optimize the use of available natural resources.